Prevalence of Malocclusion and Orthodontic Treatment Needs in Mixed Dentition of School Going Children of Dharan, Nepal - Agrawal, Sapna; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha; Bhagat, Tarakant; Niraula, Surya Raj (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Introduction: Malocclusion can be defined as a mal-relation between the dental arches in any planes beyond the normal limits. With the rise in concern about good dental appearance, people compare it with success in different fields of life and are always willing to pursue the orthodontic treatment. Objectives: To determine the prevalence of malocclusion and orthodontic treatment needs according to gender, race and age in mixed dentition of school going children of Dharan, Nepal. Methods: A cross sectional study was conducted among 830 school children from 10 randomly selected schools from January 2017 to December 2017. The type of malocclusion was determined using a structured questionnaire and the orthodontic treatment need was calculated based on Dental Aesthetic Index (DAI). Chi-square test was used to test the associations. Results: The prevalence of Class I, Class II division 1, Class II division 2 and Class III malocclusion was 49.11%, 11.43%, 4.03%, and 12.24%, respectively. Normal occlusion was found in 5.79% and 17.39% had asymmetry. The prevalence of orthodontic treatment needs was: 70.06% for slight or no need, 18.67% for elective need, 7.76% for highly desirable need, and 3.52% for mandatory need. Class I malocclusion was statistically significant for both Caucasians and Mongolians and among 8-year-old children (P≤0.001) whereas, 6-and-7-year-old children had no need for orthodontic treatment which was significant (P<0.05). Conclusion: The study highlights the prevalence of malocclusion to be high with Class I being the most common and nearly one third in need for treatment as assessed by the DAI.